Pengaruh Strategi Pembelajaran Peningkatan Kemampuan Berpikir (SPPKB) Terhadap Keaktifan Belajar Pendidikan Agama Kristes (PAK) Dan Budi Pekerti Siswa Kelas XII SMK N 1 Laguboti Tahun Ajaran 2023/2024 - Susi E Silalahi; Malani Simanungkalit; Elsina Sihombing; Lasmaria Lumbantobing; Rawatri Sitanggang (LPPM Politeknik Pratama, 2023)
The aim of this research is to determine the positive and significant influence of the Learning Strategy for Improving Thinking Ability (SPPKB) on students' active learning in class XII of SMK Negeri 1 Laguboti for the 2023/2024 academic year. The research method used is a quantitative inferential statistical method. The population is all class Data was collected using a positive closed questionnaire with 40 items, namely 20 items for variable 1 Laguboti 2023/2024 academic year: 1) Test analysis requirements: a) positive relationship test obtained rxy = 0.627> rtable(a=0.05,n=35)=0.334. b) Testing a significant relationship obtained tcount= 4.621> ttable(a=0.05,dk=n-2=33)=2.042. 2) Test the effect: a) Test the regression equation, obtained the regression equation Y ̂=